Technical Parameters of Biostimulant Spraying a Determinant of Biometric Traits and Yield of Soybean Seeds (Agricultural Engineering, 2021)
Spraying with various types of agrochemical substances, including biostimulants, is one of the basic agricultural treatments affecting the yield size and quality. The selected type of spraying nozzles can influence biological effectiveness of the applied substances. A 2-year field study showed which of the investigated nozzles increase the effectiveness of foliar application of a free amino acid biostimulant. The type of nozzle used for the application of biostimulants was reported to significantly influence the biometric properties and yield of soybean cultivation. It was observed that spraying nozzles, which generate finer droplets positively influence positively the biometric properties of plants and seed yield of seed than injector nozzles, which produce coarser droplets. A significant reduction of the thousand seeds mass after applying the biostimulant with standard flat fan nozzles is an exception. A 25.61% increase in soybean yield was reported after applying the biostimulant with standard flat fan nozzles and a 11.35% increase – with injector nozzles.